Pengendalian Kualitas Keripik Pisang Menggunakan Statistical Process Control di UD. Manalagi Jombang - Via Ade Lestariana; Rahmat Dhandy; Ahmad Haris Hasanuddin Slamet; Sekar Ayu Wulandari; Cindiah Syahnaz (Fakultas Pertanian Universitas Almuslim Bireuen Aceh, 2026)
UD. Manalagi Jombang is a micro-scale banana chips producer that does not yet implement a documented quality control system. This condition creates product defects such as broken, burnt, and unclean chips, which reduce quality and competitiveness. This study aimed to analyze banana chips quality control using Statistical Process Control (SPC) and to identify factors affecting product quality. The study employed a descriptive quantitative approach through direct observation of 20 production periods with a sample of 5,000 grams per period. The analysis used check sheets, np control charts, Pareto diagrams, cause-and-effect diagrams, and process capability analysis. The results showed that total defects reached 10.05% of the total sample, with broken chips as the dominant defect, accounting for about 45%–46% of all defects. Human factors were the main cause, especially rough handling and inadequate worker training. The process capability value for broken chips was 0.956, indicating that the process had not fully met the expected quality standard. SPC can support process monitoring, identify improvement priorities, and provide data-based quality control recommendations for food MSMEs.